2011
DOI: 10.1016/j.jadohealth.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Environmental Factors Associated With Pubertal Development in Female Adolescents: The Role of Prepubertal Tobacco and Alcohol Use

Abstract: Purpose-Alcohol administered to laboratory animals has been shown to suppress pubertyrelated hormones and delay puberty by interfering with ovarian development and function. The effects of early substance use on human pubertal development are relatively unexplored.Methods-This cross-sectional study of 3106 females, ages 11-21, evaluates the association between prepubertal alcohol and tobacco use and onset of puberty. Ages at initial breast development, body hair growth and menarche were self-reported. Prepuber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Other investigators have shown that the administration of anti‐DYN caused increased serum LH, and that a kappa opioid receptor (KOR‐1) antagonist increased the pulsatile secretion of LH and advanced puberty . Conversely, we revealed that prepubertal alcohol administration stimulates the hypothalamic synthesis and secretion of DYN; hence, DYN is suggested to be an important component of the prepubertal inhibition in GnRH/LH release that accompanies the delayed pubertal development in rats, monkeys and humans caused by chronic alcohol use.…”
Section: Introductionmentioning
confidence: 50%
“…Other investigators have shown that the administration of anti‐DYN caused increased serum LH, and that a kappa opioid receptor (KOR‐1) antagonist increased the pulsatile secretion of LH and advanced puberty . Conversely, we revealed that prepubertal alcohol administration stimulates the hypothalamic synthesis and secretion of DYN; hence, DYN is suggested to be an important component of the prepubertal inhibition in GnRH/LH release that accompanies the delayed pubertal development in rats, monkeys and humans caused by chronic alcohol use.…”
Section: Introductionmentioning
confidence: 50%
“…Alcohol (ALC) is known to diminish the secretion of LHRH and delay signs associated with the onset of female puberty in rodents (Dees and Skelley, 1990) and primates (Dees et al, 2000; Dissen et al, 2004), including humans (Peck et al, 2011; Richards and Oinonen, 2011). Specifically, these studies show that in rodents ALC delays vaginal opening (VO) markedly beyond the time when controls show VO, in primates, it significantly delays the development of regular monthly pattern of menstruation, and in human, it causes delayed breast development and menarche.…”
Section: Introductionmentioning
confidence: 99%
“…Gonadotropin releasing hormone (GnRH) stimulation tests, nuclear magnetic resonance and physical examinations were performed to exclude clinical, radiological or biochemical evidence of congenital hypogonadism syndrome, endocrinopathy, chronic disease or skeletal dysplasia. We excluded 13 boys with alcohol abuse or tobacco smoking (Peck et al, 2011). Our subjects comprised 57 cases and 110 controls.…”
Section: Subjects Recruitmentmentioning
confidence: 99%